PLPP/CIN Regulates Seizure Activity by the Differential Modulation of Calsenilin Binding to GluN1 and Kv4.2 in Mice - Kim, Ji-Eun; Hyun, Hye-Won; Min, Su-Ji; Lee, Duk-Shin; Jeon, A Ran; Kim, Min Ju; Kang, Tae-Cheon (Frontiers in Molecular Neuroscience, 2017)
Calsenilin (CSEN) binds to Kv4.2 (an A-type K+ channel) as well as N-methyl-D-aspartate receptor (NMDAR), and modulates their activities. However, the regulatory mechanisms for CSEN-binding to Kv4.2 or NMDAR remain elusive. Here, we demonstrate the novel role of pyridoxal-5'-phosphate phosphatase/chronophin (PLPP/CIN), one of the cofilin-mediated F-actin regulators, in the CSEN binding to Kv4.2 or GluN1 (a NMDAR subunit). PLPP/CIN dephosphorylated CSEN in competition with casein kinase 1, independent of cofilin dephosphorylation. As compared to wild-type mice, PLPP/CIN transgenic (PLPP/CINTg) mice showed the enhancement of Kv4.2-CSEN binding, but the reduction in CSEN-GluN1 binding. In addition, PLPP/CINTg mice exhibited the higher intensity (severity), duration and progression of seizures, but the longer latency of seizure on-set in response to kainic acid. PLPP/CIN knockout mice reversed these phenomena. Therefore, we suggest that PLPP/CIN-mediated CSEN dephosphorylation may play an important role in the functional coupling of NMDAR and Kv4.2, which regulates the neuronal excitability.